2010
DOI: 10.3340/jkns.2010.47.5.352
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Lumbar Interbody Fusion with Stand-Alone Interbody Cage in Treatment of Lumbar Intervertebral Foraminal Stenosis : Comparative Study of Two Different Types of Cages

Abstract: Objective : This retrospective study was performed to evaluate the clinical and radiological results of anterior lumbar interbody fusion (ALIF) using two different stand-alone cages in the treatment of lumbar intervertebral foraminal stenosis (IFS). Methods : A total of 28 patients who underwent ALIF at L5-S1 using stand-alone cage were studied [Stabilis ® (Stryker, Kalamazoo, MI, USA); 13, SynFix-LR ® (Synthes Bettlach, Switzerland); 15]. Mean follow-up period was 27.3 ± 4.9 months. Visual analogue pain scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 27 publications
(33 reference statements)
0
23
0
Order By: Relevance
“…Strube et al [28] Schimmel et al [25] Cho et al [27] Behrbalk et al [26] Original study cohort (n=) n.a.…”
Section: Sagittal Balancementioning
confidence: 99%
See 2 more Smart Citations
“…Strube et al [28] Schimmel et al [25] Cho et al [27] Behrbalk et al [26] Original study cohort (n=) n.a.…”
Section: Sagittal Balancementioning
confidence: 99%
“…Strube et al [28] Schimmel et al [25] Cho et al [27] Behrbalk et al [26] Overall complications were observed, which the authors referred to a reduced rhBMP-2 dose of 6 mg/level as opposed to 12 mg/level that was used in previous reports [74]. Burkus et al [70] in a multicenter prospective randomized trial with tapered interbody stand-alone fusion cages reported 94.5 % fusion rates in the investigational cohort and concluded that the use of rhBMP-2 can eliminate the need for harvesting iliac crest bone graft.…”
Section: Interbody Fusion Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite positive results [6], the stability of stand-alone cages has been questioned during the low muscular preloading phases when the cage has been suspected to be less stable [7]. The instability during the bone healing process is hypothesized to be one of the main reasons for pseudarthrosis [8][9][10] and subsidence [3]. Compared with standalone cage, supplementary fixation increases the stiffness and stability [3] and significantly improves the fusion rate [11].…”
Section: Introductionmentioning
confidence: 99%
“…Anterior plating has been proposed but increases blood loss and length of procedure. Furthermore, anatomical configuration in L4-L5 and L5-S1 can make it either difficult or impossible, so lower profile cages integrating anterior fixation screws were designed to facilitate these cases [10,12,14].…”
Section: Introductionmentioning
confidence: 99%